Coastal governance - Burroughs, Richard; SpringerLink (Online service). (Washington, DC Island Press, 2011)
Coastal Governance provides a clear overview of how U.S. coasts are currently managed and explores new approaches that could make our shores healthier. Drawing on recent national assessments, Professor Richard Burroughs explains why traditional management techniques have ultimately proved inadequate, leading to polluted waters, declining fisheries, and damaged habitat. He then introduces students to governance frameworks that seek to address these shortcomings by considering natural and human systems holistically. The book considers the ability of sector-based management, spatial management, and ecosystem-based management to solve critical environmental problems. Evaluating governance successes and failures, Burroughs covers topics including sewage disposal, dredging, wetlands, watersheds, and fisheries. He shows that at times sector-based management, which focuses on separate, individual uses of the coasts, has been implemented effectively. But he also illustrates examples of conflict, such as the incompatibility of waste disposal and fishing in the same waters. Burroughs assesses spatial and ecosystem-based management?s potential to address these conflicts. The book familiarizes students not only with current management techniques but with the policy process. By focusing on policy development, Coastal Governance prepares readers with the knowledge to participate effectively in a governance system that is constantly evolving. This understanding will be critical as students become managers, policymakers, and citizens who shape the future of the coasts.
Preface -- 1. Coastal Challenges -- 2. Policy Process -- 3. Wastewater -- 4. Oil -- 5. Dredging -- 6. Wetlands -- 7. Managing Coastal and Ocean Spaces -- 8. Ecosystem Governance. 9. Watersheds and Bays -- 10. Fisheries -- 11. Conclusion -- Questions for Discussion -- References -- Further Reading -- Glossary Index.
Electronic reproduction.
Keywords: Coastal zone management -- Environmental aspects -- United States; Electronic books